Evaluation of Pharmacological Profiling of Albizia Odoratissima Bark Extracts on Ethanol-Induced Hepatotoxicity in Albino Rats: Pharmaceutical Science-Medical Pharmacology - Jayachandrababu, Byna; Rajaram, S; Gupatha Bayya, M H R K; Singh, Goverdhan; R Zaveri, Jitendra (International Journal of Life Science and Pharma Research, 2022)
Alcohol consumption is a common cause of acute and chronic hepatic toxicity in patients. Discovery of novel therapeutic agents from medicinal plants is most recommended because of the presence of diverse phytochemicals. The aim of the study is to evaluate the therapeutic effect of methanolic extract of bark of Albizia odoratissima on ethanol-induced hepatotoxicity in rats. The following objectives A. odoratissima bark extract was screened for phytochemical analysis, and tests on acute toxicity and hepatoprotection using an Albino rat model were conducted. Twenty-four male albino rats were selected and divided into four groups (n=6). Animals received treatments for a period of 21 days. Normal control (Group-I) received vehicles; toxic control (Group-II) received ethanol (2 ml/kg/p.o.). Treatment groups (Groups-III and IV) received Silymarin (50 mg/kg/p.o.) and plant extract (250 mg/kg/p.o.). Biochemical parameters such as hepatic enzymes, biomarkers and histopathology were estimated to assess the severity of hepatic injury and or disease. Phytochemical analysis of extract reported the presence of secondary metabolites. Ethanol significantly increased SGPT and SGOT, ALP, TB, urea, and creatinine and significantly decreased total protein and albumin levels, indicating hepatic damage. Silymarin ameliorates all hepatic enzymes and biomarkers as compared to hepatotoxic control. Meanwhile, methanolic extract significantly decreased only SGPT, ALP, and creatinine, compared to hepatotoxic control. Histopathological examinations of silymarin and A. odoratissima revealed reduced liver inflammation. This study concludes that a 250mg/kg dose of A. odoratissima showed partial protective effects on ethanol-induced hepatotoxicity in rats as compared with silymarin.